Uv-B Radiation Responses in Antarctic Plants - Zuniga-Navarro, G; Contreras-Arredondo, R (Springer Science and Business Media Deutschland GmbH, 2025)
Antarctic plants have developed specialized resistance mechanisms to cope with extreme environmental conditions, including prolonged exposure to ultraviolet-B (UV-B) radiation due to ozone layer depletion. While UV-B radiation responses have been extensively characterized in model species, the adaptations of Antarctic flora remain largely unexplored. This perspective analyzes the UV-B response strategies in the two native vascular plants of Antarctica, Colobanthus quitensis and Deschampsia antarctica, as well as in Antarctic bryophytes, situating their responses within a broader framework of photoprotection in plants. C. quitensis primarily employs passive tolerance, based on the accumulation of UV-absorbing flavonoids and structural modifications that reduce radiation penetration, minimizing metabolic costs. In contrast, D. antarctica exhibits an active resistance strategy, characterized by the dynamic regulation of antioxidant enzymes and DNA repair mechanisms to mitigate oxidative stress. Antarctic mosses integrate a mixed resistance strategy, combining pigment accumulation with inducible antioxidant and DNA repair responses, allowing them to adjust their defenses based on environmental conditions. The differentiated strategies observed in these species highlight the diversity of adaptations to UV-B radiation in extreme environments. This perspective discusses the ecological implications of these resistance mechanisms and identifies key knowledge gaps for future research. Exploring the genetic and biochemical regulation of UV-B radiation responses in Antarctic plants could provide valuable insights for biotechnological applications, particularly in developing crops more resilient to increasing UV-B exposure under climate change scenarios. © The Author(s), under exclusive licence to Brazilian Society of Plant Physiology 2025.